Illuminating the life of the Buddha an illustrated chanting book from eighteenth-century Siam - Appleton, Naomi 1982-; Shaw, Sarah; Unebe, Toshiya (Bodleian Library, University of Oxford, 2013)
"This lavishly illustrated book investigates an outstanding eighteenth-century example of a samut khoi, a type of beautiful folding book found in Southeast Asia, which became particularly popular as a repository for the Buddha's teachings. Written in Pali and produced in the Kingdom of Siam, its finely executed pictures, painted on khoi paper, show key incidents from stories of the past lives of the Buddha as he prepares for Buddhahood. These tales, historically one of the principal means whereby Buddhist teachings were communicated, known as Jatakas, are a favourite theme for manuscript art. Uniquely for such manuscripts, however, this samut khoi also offers an extensive series of scenes from the last life of the Buddha, including his final awakening and teaching, which is distinctive to the region. These related narratives all contribute to a superb example of eighteenth-century manuscript and calligraphic art. As well as affording great artistic opportunities for expressing the beauty of the Buddha's words and achievements, samut khois are repositories for popular chants and short distillations of doctrine. This book describes the context to this unusually rich expression of Thai Buddhist creativity and, in retelling the stories depicted, reveals the continued appeal of its closely related art and narrative traditions." -- Publisher's description.